A Case Report Highlighting Rapid Graft Function and Structured Perioperative Management in End-Stage Renal Disease - Frihadananta, Ridho; Wibisono, Wibisono (Syntax Literate, 2025)
Background: Kidney transplantation is the treatment of choice for patients with chronic kidney disease (CKD) that progresses to end-stage renal disease (ESRD). Epidemiological data from the last decade show that the global burden of kidney failure patients receiving renal replacement therapy exceeds 1.4 million and this figure is increasing by about 8% per year. This procedure can improve quality of life and social functioning in patients with ESRD and can reduce treatment costs compared to patients who only do dialysis for the first 3 years after the transplant procedure. The main goal of postoperative care is to ensure stable hemodynamics provide optimal perfusion for the newly transplanted kidney along with good analgesia during the recovery period. Case Presentation: A 43-year-old man who has a history of hypertension and CKD on HD since 2023 (performed routinely HD 2 times a week) underwent kidney transplant surgery. There were no complications after the kidney transplant procedure with serum ureum 39 mg / dL and creatinine 1.4 mg / dL. Discussion: Patients with CKD are eligible for donor kidney transplantation when the eGFR is less than 20 ml/min/1.73m2. Patients with a history of routine HD 2 times a week with serum urea 164 mg / dL, creatinine 18.8 mg / dL, and potassium 6.0 mmol / L preoperatively then after kidney transplantation and postoperative care obtained serum ureum 39 mg / dL, creatinine 1.4 mg / dL, and potassium 4.3 mmol / L. Preoperative preparation and postoperative care in patients with kidney transplantation are critical to the success of the kidney transplant program itself. Conclusion: Kidney transplantation has improved survival and quality of life of patients with end-stage kidney disease.